СИСТЕМНОЕ СУБКЛИНИЧЕСКОЕ ВОСПАЛЕНИЕ И ФУНКЦИОНАЛЬНЫЙ СТАТУС ПАЦИЕНТОВ С ХОБЛ И ХСН - Главатских, Ю О; Токмачев, Р Е; Дробышева, Е С; Овсянников, Е С; Гречкин, В И; Черник, Т А; Механтьева, Л Е; Токмачев, Е В; Шкатова, Я С; Будневский, А В (FORCIPE, 2021)